2021
DOI: 10.1111/bre.12550
|View full text |Cite
|
Sign up to set email alerts
|

Principles of shortening in salt basins containing isolated minibasins

Abstract: Shortening styles in salt-influenced basins can vary markedly, with the volume and distribution of salt prior to shortening being a key control. Here, we use a suite of physical models to examine styles of thin-skinned regional shortening in settings where the preshortening structure comprised minibasins surrounded by salt ('isolated- Highlights• In settings with isolated minibasins and a high salt volume, shortening induces salt flow.• The flow of salt contributes to the translation, tilt and rotation of mini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…After large‐transport thrusting, deformation transferred to the salt wall‐minibasin province. There, contractional deformation focusses on salt walls whereas minibasins are translated, jostled and eventually collided (Duffy et al., 2017, 2021) and rotated (Callot et al., 2016; Duffy et al., 2021; Ferrer, 2012; Rowan & Vendeville, 2006; Santolaria, Granado, et al., 2021) whilst broadly preserving their original architecture (Rowan & Vendeville, 2006). During salt wall squeezing, inherited roof thickness played a significant role.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After large‐transport thrusting, deformation transferred to the salt wall‐minibasin province. There, contractional deformation focusses on salt walls whereas minibasins are translated, jostled and eventually collided (Duffy et al., 2017, 2021) and rotated (Callot et al., 2016; Duffy et al., 2021; Ferrer, 2012; Rowan & Vendeville, 2006; Santolaria, Granado, et al., 2021) whilst broadly preserving their original architecture (Rowan & Vendeville, 2006). During salt wall squeezing, inherited roof thickness played a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…Squeezing results in salt wall closure and secondary welding (e.g., Nilsen et al., 1995; Vendeville & Nilsen, 1995; Rasmussen et al., 1998; Ferrer, 2012; Roma, Ferrer, et al., 2018; Santolaria, Ferrer, et al., 2021; this work). Squeezing of vertical salt walls flanked by trough‐like minibasins results in relatively simple secondary welds, commonly localized along the maximum lateral expansion of minibasins (Duffy et al., 2021; Ferrer, 2012; Roma, Ferrer, et al., 2018; Rowan & Vendeville, 2006; Santolaria, Granado, et al., 2021). Conversely, in our models, the uneven inherited geometry of the salt walls and their flanks led to variable secondary weld geometries and tectonostratigraphic relations: interdigitated diapir shoulders and wings (Figures 11c and 11b), pinched secondary minibasins (Figure 8b) and welds that put in contact younger sequences with the oldest layers of the modeling package (Figure 8c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sediment input and loading direction had shifted from the east to the NW and had caused the formation of mini‐basins to the northwest and intense salt evacuation to the south together with the rotation of the mini‐basins where base‐salt relief also facilitated the differential salt flow (Figures 13A3–B3, 14A9–A11, and 15A3–B3). The mini‐basin rotation also depends on the progradational sedimentation direction and contraction (Figures 8b,c and 9b) (Callot et al., 2016; Duffy et al., 2021; Fernandez et al., 2020). The salt depletion and sediment accumulation were now mainly focused in the CNB segment, and were gradually minimised within the NENB and SWNB segments (Figure 6b; Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of minibasins, recent studies have shown how minibasins exhibit complex subsidence and rotation histories as a result of, amongst others: tectonic shortening, interactions with base-salt relief, translation down salt-detached slopes, and mechanical interactions with other minibasins (e.g. Fernandez et al, 2020;Jackson et al, 2020;Duffy et al 2021). Such processes will have significant implications and thus should be constrained when reconstructing minibasin palaeo-topography.…”
Section: Salt Tectonic Influence On Reservoirmentioning
confidence: 99%